NUCKS nuclear elevated expression indicates progression and prognosis of ovarian cancer - Ce Shi; Ling Qin; Hongyu Gao; Lina Gu; Chang Yang; Hebing Liu; Tianbo Liu (Tumor Biology)
NUCKS (nuclear, casein kinase, and cyclin-dependent kinase substrate) is implicated in the tumorigenesis of several human malignancies, but its role in ovarian cancer remains unknown. We aim to investigate NUCKS expression and its clinical significance in ovarian cancer. The messenger RNA expression of NUCKS was determined in normal and malignant ovarian tissues using quantitative polymerase chain reaction assay. Immunohistochemistry was applied to detect the status of NUCKS protein expression in 121 ovarian cancer tissues. NUCKS protein high expression was detected in 52 (43.0%) of 121 patients. NUCKS messenger RNA expression was gradually upregulated in non-metastatic ovarian cancers ( n  = 20), metastatic ovarian cancers ( n  = 20), and its matched metastatic lesions ( n  = 20) in comparison with that in normal ovarian tissues ( n  = 10; p  < 0.05). Elevated expression of NUCKS in ovarian cancer was associated significantly with the Federation of Gynecology and Obstetrics stage ( p  = 0.037), histological grade ( p  = 0.003), residual disease ( p  = 0.013), lymph node metastasis ( p  = 0.002), response to chemotherapy ( p  < 0.001), and recurrence ( p  = 0.013). In the multivariate Cox analysis, NUCKS expression was an independent prognostic marker for overall survival and disease-free survival in ovarian cancer with p values of <0.001 for both. Especially, NUCKS overexpression had prognostic potential for overall survival and disease-free survival ( p  < 0.001 for both) in advanced ovarian cancers and only for disease-free survival in early ovarian cancers ( p  = 0.017). Our data suggest that NUCKS overexpression may contribute to progression and poor prognosis in ovarian cancer especially in advanced ovarian cancer.